Observation of the B0→D[bar]*0K+π− and B0s→D[bar]*0K−π+ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2022)
The first observations of B0→¯D∗(2007)0K+π− and B0s→¯D∗(2007)0K−π+ decays are presented, and their branching fractions relative to that of the B0→¯D∗(2007)0π+π− decay are reported. These modes can potentially be used to investigate the spectroscopy of charm and charm-strange resonances and to determine the angle γ of the Cabibbo-Kobayashi-Maskawa unitarity triangle. It is also important to understand them as a source of potential background in determinations of γ from B+→DK+ and B0→DK+π− decays. The analysis is based on a sample corresponding to an integrated luminosity of 5.4 fb−1 of proton-proton collision data at 13 TeV center-of-mass energy recorded with the LHCb detector. The ¯D∗(2007)0 mesons are fully reconstructed in the ¯D0π0 and ¯D0γ channels with the ¯D0→K+π− decay. A novel weighting method is used to subtract background while simultaneously applying an event-by-event efficiency correction to account for resonant structures in the decays.